THE HIGH-PERFORMANCE PLAYBOOK: STRATEGIES FOR MOTIVATING AND RETAINING TOP TALENT - Synthia; Ramon Zamora; Lukmanul Hakim (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This article addresses the critical business challenge of employee retention in the competitive modern talent market. The objective is to provide a systematic, actionable framework for organizations to motivate and retain their highest performers. The methodology synthesizes contemporary management research, organizational psychology principles, and best practices from industry case studies into a cohesive "playbook." The proposed strategies are organized into four foundational pillars: cultivating a culture of purpose and psychological safety, fueling personalized growth, optimizing performance through clarity and feedback, and implementing holistic recognition. The discussion emphasizes that retention is a strategic outcome of a holistic employee experience, moving beyond transactional perks. The conclusion posits that by architecting an ecosystem where top talent can thrive, organizations secure a sustainable competitive advantage through enhanced innovation, stability, and performance, ultimately transforming retention from an HR metric into a core leadership responsibility.